Tailor-made high-performance reverse osmosis membranes by surface fixation of hydrophilic macromolecules for wastewater treatment. Issue 31 (6th June 2019) - Liu, Chao; Guo, Yongqiang; Zhang, Jiaming; Tian, Bo; Lin, Oukai; Liu, Yawei; Zhang, Chunhua
Abstract : Polyamide aromatic (PA) reverse osmosis (RO) membranes are currently the most important materials in the seawater desalination and wastewater treatment industry. Abstract : Polyamide aromatic (PA) reverse osmosis (RO) membranes are currently the most important materials in the seawater desalination and wastewater treatment industry. This study used hydrophilic macromolecular polyvinylpyrrolidone (PVP) in a PA selective layer to develop a new polyamide thin-film composite (TFC), namely PA- g -PVP RO, which will be used for water treatment. The TFC is prepared via an interfacial polymerisation process, and TFC-based PVP can be transplanted on a PA surface by radiation. PA- g -PVP RO was characterised by ATR-FTIR, SEM, XPS, AFM and contact angle test and then evaluated by determining its permeability, salt retention and antifouling performance, among other properties. Results show that the chemical composition and surface morphology of the polyamide film significantly changed. A PVP brush grafted on an RO membrane surface significantly enhanced the hydrophilicity and antifouling performance of the membrane. When the PVP concentration was increased in an aqueous solution to 2%, the water contact angle of the sacrificial layer of the modified membrane decreased to 24.3°, the fouling recovery ratio to 93.4% and the salt retention increased to 99.5% at a small flux change. This combined technology can also be used for other macromolecules to modify the membrane and study the preparation and modification of ultra-filtration and nano-filtration membranes.